2016
DOI: 10.18203/issn.2455-4510.intjresorthop20162886
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of displaced acetabular fractures in adults treated with open reduction and internal fixation

Abstract: <p class="abstract"><strong><span lang="EN-US">Background: </span></strong>The incidence of acetabular fractures is increasing worldwide at a rapid rate due to increase in rail and road traffic accidents and high velocity injuries. The incidence of acetabular fractures is increasing worldwide at a rapid rate due to increase in rail and road traffic accidents and high velocity injuries.</p><p class="abstract"><strong><span lang="EN-US">Methods:</span>&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…11(28%). The same were also experienced in their study by Hussain, et al [1]. In our study we found that open reduction and internal fixation was the preferred and major management practices for the patient.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…11(28%). The same were also experienced in their study by Hussain, et al [1]. In our study we found that open reduction and internal fixation was the preferred and major management practices for the patient.…”
Section: Discussionsupporting
confidence: 85%
“…Acetabular fractures occur when the head of femur is pushed into the pelvis by a lateral blow to the hip or by an anterior blow to the knee with hip in flexion and abduction [1]. Acetabulum fracture has rare incidence of about 5/100,000 people per year, as compared to proximal femur fractures, which has about a hundred times higher incidence, based on geographical areas [2].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study concludes that delay in surgical reconstruction of acetabular fractures has worse effect on outcome2122). We evaluate the effect of delay in surgical reconstruction on outcome by dividing patients into two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has become obvious that accurate reduction of the fracture is an important factor in achieving satisfactory outcome and open reduction is better than closed reduction which resulted in incongruence of articular surface of hip joint and patients were left with enormous pain and end result stiff and painful suboptimal functioning hip joint. 2,3 The treatment of simple fractures of acetabulum is well known and studied. Treatment of complex Acetabular fracture is difficult as it involves both the column of the acetabulum, for reduction and fixation, both columns have to manipulated and fixed.…”
Section: Introductionmentioning
confidence: 99%